1997
DOI: 10.1016/s0020-7292(97)00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and prevalence of pre‐eclampsia, Norway 1989

Abstract: Prenatal care should include assessment of working conditions, as early improvements may reduce the risk of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 14 publications
4
41
2
2
Order By: Relevance
“…(40) Second, the frequency and effect of other known risk factors (e.g., gravidity, number of fetuses, and maternal weight) are similar to those consistently reported in the literature, (41) and the associations with coffee intake and early menarche were also described in two previous publications. (42,43) Other previously suggested risk factors, such as advanced maternal age, diabetes, and Black race, were not associated with a higher frequency of gestational hypertension in our study; most likely because we excluded women with chronic hypertension (i.e., these factors were associated with hypertension diagnosed before 20 weeks of gestation). Our failure to find the previously suggested protective effect of smoking(44) might be due to differences among populations, methodological factors, or/and chance.…”
Section: Discussionmentioning
confidence: 66%
“…(40) Second, the frequency and effect of other known risk factors (e.g., gravidity, number of fetuses, and maternal weight) are similar to those consistently reported in the literature, (41) and the associations with coffee intake and early menarche were also described in two previous publications. (42,43) Other previously suggested risk factors, such as advanced maternal age, diabetes, and Black race, were not associated with a higher frequency of gestational hypertension in our study; most likely because we excluded women with chronic hypertension (i.e., these factors were associated with hypertension diagnosed before 20 weeks of gestation). Our failure to find the previously suggested protective effect of smoking(44) might be due to differences among populations, methodological factors, or/and chance.…”
Section: Discussionmentioning
confidence: 66%
“…One previous study showed a positive association between heavy lifting (10-20 kg or 22-44 lb) in early pregnancy (occurring more than 20 times per week) and preeclampsia. 24 Additionally, a 2-fold increased risk of preeclampsia was found for pregnant women with high physical activity at work (composite score). 7 An explanatory model by Paul et al 25 (1994) suggests that pregnancy-related musculoskeletal problems arise, at least in part, from reduced load-bearing capacity associated with joint laxity.…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
“…One previous study showed a positive association between heavy lifting (10-20 kg or 22-44 lb) in early pregnancy (occurring more than 20 times per week) and preeclampsia. 24 Additionally, a 2-fold increased risk of preeclampsia was found for pregnant women with high physical activity at work (composite score). 7…”
mentioning
confidence: 99%
“…Recent reports, studying women working night shifts (in services such as healthcare, military, protection and airway), show associations between disrupting the light-dark cycle during pregnancy and a higher risk of PTB, low birth weight, spontaneous abortion and subfertility (Knutsson, 2003;Mahoney, 2010;Waddell et al, 2012). So far, however, only a few data are available on associations between alterations of the circadian rhythm and PE (Ditisheim et al, 2013;Haelterman et al, 2007;Mozurkewich et al, 2000;Wergeland & Strand, 1997). In this regard of interest is the hormone melatonin, which is regulated by the circadian clock and synthesized by the placenta thereby protecting against excessive oxidative stress involved in the pathogenesis of PE (Chen et al, 2013;Hobson et al, 2013;Valenzuela et al, 2015).…”
Section: Introductionmentioning
confidence: 99%